Emotional Intelligence in Soft Skills: First-Class Human Domain Generating - Johar, Siti Sarawati (International Journal of Engineering and Technology, 2018)
The focus in this short study is to clarify the soft skills development by the emotional intelligence standpoint purposing for generate the first-class human domain (emotional, mentality and behaviour) as a human capital. Discussion on issues of human development scenario, the importance of emotional intelligence and the importance of soft skills will discuss in detail. The year 2020 is targeted by Malaysia to becoming a developed country with our own way. The exact aspiration is to develop the ideal human capital in balance with the emotional intelligence and acceptable mindset fitting the way of life from one generation to one generation. The stable country’s development in politic, economic and social field are significant to human value as mentioned in Maslow’s theories. Many of world civilizations always noted by the best achievement in the fact of physically facilities, infrastructures, level of literacy, stable economic status and political that able to influence the world order. Unfortunately, some of world society lives in absent of holistic value, inconsiderate, depression and lack of religion grasp. Historically Malaysia has been colonized by European around 446 years. Some of social, economy and political patterns influenced the Malaysians way of living. Some actions should be considered to preserve our valuable traditions, norms, culture inherited by our relatives from different demographical background. Those values supposed as the truly image of first-class human capital incorporated with the developing and generating the art of emotional intelligence in soft skills among Malaysian students.